THE DEVELOPMENT OF LUBUK TAROK VILLAGE FROM A HIGH-RESISTANCE VILLAGE TO A TOURIST VILLAGE IN 2017-2023: Perkembangan Nagari Lubuk Tarok Dari Nagari Berprestasi Hingga Nagari Wisata Tahun 2017-2023 - Anggun Prana Dewi anggun; Meri Erawati; Felia Siska (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research aims to examine the development of Nagari Lubuk Tarok from an Award-Winning Nagari to a Tourism-Oriented Nagari, focusing on aspects of governance, culture, economy, society, and the preservation of historical heritage, as a contribution to the documentation and understanding of local history in MinangkabauThis study employed historical methods consisting of heuristic, criticism, interpretation, and historiography stages, with data collected from official documents, interviews, archives, and supporting literature, critically and systematically analyzed. By 2023, strengthened tourism institutions, digital promotion, and the development of creative economies based on local wisdom had established Lubuk Tarok as a tourist destination that integrates Minangkabau traditional values with sustainable modern development, while reinforcing the community’s identity and independence.